(untitled) (Información, cultura y sociedad, 2022)
This work presents the first results of an ongoing investigation on the historical process of the beginning, location and development of Librarianship and its teaching in the province of Entre Ríos between 1926 and 2015, finding in the Studies of Science, Technology and Society a fertile theoretical plot to account for said process that proposes the concept of constitutional moment and will allow to identify different periods through which the teaching of Librarianship passed through the process of initiation and consolidation. Concept that makes it possible to study how actors, institutions, representations, and fields of knowledge were assembled. Two constitutional moments become evident. The first involved the entry of Librarianship and its teaching in the province through the modality of courses articulated with interests for training in librarianship that had a reduced scope and mainly in private institutions, the second involved careers that offered specific degrees in library science. During these constitutional moments, ties were maintained with Librarianship both at national level (Buenos Aires and Santa Fe) and at international level (USA and Europe), accompanying its vanguard and updating itself on a deferred basis.